2016
DOI: 10.1021/acs.energyfuels.6b02293
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Two-Dimensional Natural Downward Smoldering of Peat

Abstract: Smoldering combustion of natural organic layers like peatlands leads to the largest fires on Earth. The multidimensional smoldering structure of peatlands is observed in the field, but the mechanism is poorly understood. In this work, a 2-D cylindrical axi-symmetric model that considers volume shrinkage is developed for the natural downward smoldering of peat with different inorganic contents. Numerical results show that the model captures the two-dimensional multisubfront structure of the peat smoldering proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Huang and Rein [23] explained that this is because of the faster oxygen transport due to swelling. IC, on the other hand, slightly decreases in-depth spread, according to both experiments and modelling [24,25]. Notably, as the fire moves downward, in-depth spread rate decreases with depth due to the accumulation of ash above the oxidation zone reducing the oxygen supply [23,24,26].…”
Section: Figure 1 -Illustration Of the Stages And Key Features Of Smomentioning
confidence: 68%
“…Huang and Rein [23] explained that this is because of the faster oxygen transport due to swelling. IC, on the other hand, slightly decreases in-depth spread, according to both experiments and modelling [24,25]. Notably, as the fire moves downward, in-depth spread rate decreases with depth due to the accumulation of ash above the oxidation zone reducing the oxygen supply [23,24,26].…”
Section: Figure 1 -Illustration Of the Stages And Key Features Of Smomentioning
confidence: 68%
“…This data is in contrast to Prat [18] that found a range of mass consumed of 84.3 ± 4.9% −93.7 ± 2.1% for multiple moisture contents of peat. This may occur due to the different characteristics of the peat samples and also the different insulation used in the apparatus which alters the balance between heat generation and heat lost [19].…”
Section: Smoldering Experimentsmentioning
confidence: 99%
“…As (1) the vertical dimension was clearly larger than the cross-section dimension and (2) the smouldering spread is extremely slow, the whole downward spread may be approximated as a 1-D spread phenomenon, similar to those in Benscoter et al 2011 andZaccone et al 2014). This 1-D dominated downward spread of smouldering peat fire without the wind is different from other multi-dimensional smouldering spread over small and shallow peat samples (Hadden et al 2013;Huang et al 2016;Prat-Guitart et al 2016;Yang et al 2016).…”
Section: Introductionmentioning
confidence: 96%
“…1), which plays an important role in the estimation of soil carbon emission. The DOB and critical MC for extinction ðMC Ã ex Þ at the vertical downward (or indepth) spread of peat fires have been investigated by various experiments (Benscoter et al 2011;Watts 2012;Davies et al 2013;Zaccone et al 2014) and numerical simulations Rein 2015, 2016a;Yang et al 2016). Recently, laboratory experiments on the horizontal fire spread over a shallow peat sample showed that the spread rate decreased with MC but increased with the forward wind speed (Huang et al 2016;Prat-Guitart et al 2016).…”
Section: Introductionmentioning
confidence: 99%